Neuroimaging of Intracerebral Hemorrhage. Issue 5 (28th February 2020) - Rindler, Rima S; Allen, Jason W; Barrow, Jack W; Pradilla, Gustavo; Barrow, Daniel L
Abstract: Intracerebral hemorrhage (ICH) accounts for 10% to 20% of strokes worldwide and is associated with high morbidity and mortality rates. Neuroimaging is indispensable for rapid diagnosis of ICH and identification of the underlying etiology, thus facilitating triage and appropriate treatment of patients. The most common neuroimaging modalities include noncontrast computed tomography (CT), CT angiography (CTA), digital subtraction angiography, and magnetic resonance imaging (MRI). The strengths and disadvantages of each modality will be reviewed. Novel technologies such as dual-energy CT/CTA, rapid MRI techniques, near-infrared spectroscopy, and automated ICH detection hold promise for faster pre- and in-hospital ICH diagnosis that may impact patient management.